Evolution of rural communities through homestay programs: A case study of Banghuris Homestay - Othman, Muhammad Hanif; Mohamad, Noorihsan; Ghani, Gairuzazmi; Ariffin, Muhammad Irwan (Universiti Utara Malaysia, 2017)
The development of rural tourism has always been considered as one of the important agendas of Malaysia development. Over the past decades, many strategies and programs were introduced by the government to eradicate the issue of poverty in among rural communities. The strategy to bring together rural communities in community-based tourism is one of them. Through the communities’ participation in homestay program, it is expected that the rural villagers could benefit in diversifying their source of income. To date, the homestay program in Malaysia has grown tremendously and has become as one of the main tourism products. In general, the homestay programs not only benefited the operators but also the surrounding communities. This paper explores the impact of homestay programs that were extended to the local and nearby communities using a specific case study of the Banghuris area in Sepang, Selangor. Using quantitative design, data from the respondents were analyzed using the principal component analysis in determining the dominant impacts to rural communities. The finding shows that homestay programs has positively affected the surrounding communities especially in terms of environment, economy, social and culture. Furthermore, this homestay program can also solve rural problems which are on improving public facilities, accessibility and employment opportunity.